A Neglected Swollen Limb: Resurgence or Common Tropical Disease? - Ray, Sumit; Pathak Thapa, Deeptara (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Mycetoma is uncommon, chronic granulomatous infection caused either by fungi or by aerobic filamentous actinomycetes which is characterized by a triad of painless subcutaneous mass, multiple sinuses and discharge containing grains. We report a case of 40 years old male, farmer who presented with multiple painless swollen lesions over right foot for 8 years. Swelling had gradually increased in size over a few years followed by multiple episodes of discharge. It had not restricted his daily activities. On examination, there were multiple nodules and sinuses discharging serous fluid from the right foot. Gram staining showed gram positive filamentous rods and KOH was negative. Histopathology showed multiple granulomas. Patient was treated for 5 cycles using modified Welsh regimen with Amikacin 750mg intravenously once a day, oral Cotrimoxazole 960mg twice daily and oral Rifampicin 600mg once daily along with oral iron and folic acid supplementation continuously for 21days which constituted 1 cycle with an interval of 15 days between each cycle. Patient was assessed by measuring girth of foot and number of lesions in each visit and showed significant improvement at the end of fifth cycle. Patient was followed for 1 year after treatment without any recurrence.